Biocontrol potential of lipopeptides produced by the novel Bacillus subtilis strain Y17B against postharvest Alternaria fruit rot of cherry - Ahmad, Tanvir; Xing, Fuguo; Nie, Chengrong; Cao, Changyu; Xiao, Ying; Yu, Xi; Moosa, Anam; Liu, Yang (Frontiers in Microbiology, 2023)
The use of synthetic fungicides against postharvest Alternaria rot adversely affects human health and environment. In this study, as a safe alternate to fungicides, Bacillus subtilis strain Y17B isolated from soil exhibited significant antifungal activity against Alternaria alternata. Y17B was identified as B. subtilis based on phenotypic identification and 16S rRNA sequence analysis. To reveal the antimicrobial activity of this strain, a PCR-based study detected the presence of antifungal lipopeptides (LPs) biosynthetic genes from genomic DNA. UPLC Q TOF mass spectrometry analysis detected LPs; surfactin (m/z 994.64, 1022.68 and 1026.62), iturin (m/z 1043.56), and fengycin (m/z 1491.85) in the extracted LPs crude of B. subtilis Y17B. In-vitro, antagonistic study demonstrated the efficiency of LPs for the inhibition of A. alternata growth. The microscopic (SEM and TEM) studies showed, the alteration of morphology of the A. alternata in the interaction with LPs. The in vivo test results revealed the efficiency of LPs against A. alternata to reduce pathogen growth. The overall results highlight, the biocontrol potential of LPs produced by B. subtilis Y17B as an effective biological control agent against the A. alternata caused fruit rot of cherry.